Development and fabrication of ammonia gas leakage detection and monitoring system - Ibrahim, Rosli (2022)
In industries that use hazardous gases in significant amounts for their diverse processes, there are high-risk variables involved. People may fail to detect or monitor the emission of these gases on a regular basis before it becomes dangerous. Sensors are required to continuously monitor leaks and notify users to potential hazards. The purpose of the project is to improve irrelevant measurement methods that are held or installed on walls and serve merely to measure. The project incorporates Internet-of-Thing’s technology to monitor sensor readings from a safe distance, locate areas where ammonia gas is leaking based on pressure sensor readings, and includes a prevention system that serves as feedback that responds to sensor readings to control water pumps, fans, and solenoid valves to control ammonia gas leakage. Various sensor values are received and processed using microprocessors. This project design and fabrication of an ammonia gas leakage detection and monitoring system employs the ESP 32 as a microcontroller due to its low-power, low-cost system that includes built-in Wi-Fi and dual-mode Bluetooth. The Air Quality Sensor MQ-135 also serves as an Ammonia Gas Sensor, detecting gas leakage when ammonia gas leaks. The project system focuses on the transfer of data from the sensing unit to the broker, where it is kept momentarily in the Blynk app but can be stored for a long time and exported in the web Thingspeak, as well as the GPS system, gives precise latitude and longitude information. The data is displayed on a mobile web and application, which users can use to monitor sensor readings. Data is transmitted via the nodeMCU, which reads data from inputs and outputs and sends it to Blynk applications and the Thingspeak protocol. The pressure sensor is used to identify specific parts of ammonia gas leakage. The siren alarm and LEDs are used to notify employees or officials. This ammonia gas leakage detection and monitoring system project was completed successfully. There are improvements can be done for future development on this prototype such as to fabrication ammonia plant using non corossive material and use industrial sensor to make reading for accurate ammonia gas detection.